Current Strategic Approaches In Ethnomedicinal Plants Of Tinospora Cordifolia And Gloriosa Superba – A Review - S. VEERAIAH,; K. JAGANMOHAN REDDY, (International Journal of Pharma and Bio Sciences, 2012)
Tinospora cordifolia (Guduchi) is an important drug of Ayurvedic system of medicine.It is widely grown at Western ghatts. It is used in diseases like jaundice, edema, gout, diabetes, swine flu (H1N1), hepatitis, hyper acidity, dyspepsia, fever, urinary and skin diseases. This plant contains Shicmic acid, which is isolated from plant parts and Tamiflu tablets are prepared at industrial level. Today lot of work is undertaken on it in Pharma, Biochemical, Tissue culture and Genetic engineering. Gloriosa superba L. is an important medicinal plant of Asia and Africa. It is a source of colchicines and colchicocides. It is used in diseases like gout, cancer, leprosy, swelling, piles, chronic ulcers and act as antipyretic, antidote in snake bite, anti helmintic, purgative and anti abortive. Due to excessive use of the plants for diverse medicinal purposes the species is on the verge of extinction and included in Red Data Book. The strenuous efforts of botanists, biotechnologists and conservationists are required to conserve these plants; otherwise we will be loosing it by 2020. The present review is focused on current status of those Ethnomedicinal values, source of alkaloids, poisonous nature, conservation and future perspectives of T. cordifolia and G.superba.